Comparing eating disorder characteristics and treatment in self‐identified competitive athletes and non‐athletes from the National Eating Disorders Association online screening tool. Issue 3 (30th November 2020) - Flatt, Rachael E.; Thornton, Laura M.; Fitzsimmons‐Craft, Ellen E.; Balantekin, Katherine N.; Smolar, Lauren; Mysko, Claire; Wilfley, Denise E.; Taylor, C. Barr; DeFreese, J. D.; Bardone‐Cone, Anna M.; Bulik, Cynthia M.
Abstract: Objective: We compared eating disorder (ED) characteristics and treatment seeking behaviors between self‐identified competitive athletes and non‐athletes in a large, community‐based sample. Method: During the 2018 National Eating Disorders Awareness Week, 23, 920 respondents, 14.7% of whom identified as competitive athletes, completed the National Eating Disorders Association online screen. Data were collected on demographics, disordered eating behaviors, probable ED diagnosis/risk, treatment history, and intent to seek treatment. Results: The sample was predominantly White (81.8%), female (90.3%), and between 13 and 24 years (82.6%). Over 86% met criteria for an ED/subthreshold ED, and of those, only 2.5% were in treatment. Suicidal ideation was reported in over half of the sample. Athletes reported a significantly greater likelihood of engaging in and more frequent excessive exercise episodes than non‐athletes. Athletes also reported a significantly lower likelihood of engaging in and less frequent binge‐eating episodes compared with non‐athletes. Athletes were more likely to screen positive for an ED/subthreshold ED than non‐athletes, but percentages across all probable ED diagnoses were similar. No significant differences between athletes and non‐athletes emerged on treatment history or intention to seek treatment post‐screen (less than 30%). Discussion: Although the distribution of probable ED diagnoses was similar in athletes and non‐athletes, symptom profiles related to disordered eating behavior engagement and frequency may differ. Athletes may be less likely to seek treatment due to stigma, accessibility, and sport‐specific barriers. Future work should directly connect survey respondents to tailored treatment tools and increase motivation to seek treatment.